PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN PADLET TERHADAP MINAT BELAJAR SISWA PADA MATA PELAJARAN BIOLOGI DI SMAN 7 SINJAI - Fitrah Wahyuni; Mudeing Jais; Nurdin (STKIP Subang, 2024)
This research aims to determine the effect of using Padlet Media on students' interest in learning at SMAN 7 Sinjai. This type of research is quantitative or experimental research (Pre Experiment) with a Post-test One Shot Case Study design. The population in this study were all students of class XI Mipa SMAN 7 Sinjai which consisted of 3 classes with a total of 80 students. The sample in this research was class XI A1 students with a total of 27 students, who were selected through Cluster Sampling. Data collection techniques in this research are observation, questionnaires and documentation